An arginine decarboxylase gene PtADC from Poncirus trifoliata confers abiotic stress tolerance and promotes primary root growth in Arabidopsis - Wang, Jing (Journal of experimental botany, 2011)
Arginine decarboxylase (ADC) is an important enzyme responsible for polyamine synthesis under stress conditions. In this study, the gene encoding ADC in Poncirus trifoliata (PtADC) was isolated and it existed as a single-copy member. Transcript levels of PtADC were up-regulated by low temperature and dehydration. Overexpression of PtADC in an Arabidopsis thaliana ADC mutant adc1-1 promoted putrescine synthesis in the transgenic line and the stomatal density was reverted to that in the wild type. The transgenic line showed enhanced resistance to high osmoticum, dehydration, long-term drought, and cold stress compared with the wild type and the mutant. The accumulation of reactive oxygen species (ROS) in the transgenic line was appreciably decreased under the stresses, but ROS scavenging capacity was compromised when the transgenic plants were treated with the ADC inhibitor D-arginine prior to stress treatment. In addition, the transgenic line had longer roots than the wild type and the mutant under both normal and stressful conditions, consistent with larger cell number and length of the root meristematic zone. Taken together, these results demonstrated that PtADC is involved in tolerance to multiple stresses, and its function may be due, at least partly, to efficient ROS elimination and to its influence on root growth conducive to drought tolerance